Optimalisasi Sistem Pencatatan Keuangan Berbasis SIA pada OK Futsal - S, Suharyono (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Digital transformation in financial management has become an urgent necessity for small business actors, including sports service enterprises such as OK Futsal. This study aims to analyze the implementation of an Accounting Information System (AIS) in optimizing financial reporting at OK Futsal, located in Bagan Melibur Village, Kepulauan Meranti Regency. The research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation during the 2024 mentoring period. The results indicate that the application-based AIS has facilitated the preparation of financial reports in a more systematic and accurate manner and has served as a reliable basis for business decision-making. The implementation of AIS has also enhanced the business owner's understanding of the importance of transaction recording, transparency, and financial accountability. This study makes a practical contribution to strengthening the managerial capacity of MSMEs and serves as a reference for similar business actors in managing finances in a modern and efficient way.